2014
DOI: 10.1007/s11239-014-1147-5
|View full text |Cite
|
Sign up to set email alerts
|

Rare reason for pulmonary embolism: one case of pulmonary hydatid cyst and review of the literature

Abstract: Pulmonary embolism due to hydatid disease has been rare clinically. Here we present a patient case who suffered from multiple cystic hydatidosis within bilateral lung parenchyma and complicated bilateral pulmonary embolisms. The case was a 70-year-old man who complained of an increasingly severe cough and hemoptysis post-operation of hepatic hydatid cyst. Chest radiographs showed that the patient had multiple nodules in the bilateral chest. Computed tomography (CT) depicted that some lesions were multivesicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Diagnosis of hydatid cysts in the lung is primarily through radiographic investigations, such as Chest X-ray and CT scan [ 4 , 6 ]. Serological tests can be useful to confirm the diagnosis, but their sensitivity and specificity are low [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosis of hydatid cysts in the lung is primarily through radiographic investigations, such as Chest X-ray and CT scan [ 4 , 6 ]. Serological tests can be useful to confirm the diagnosis, but their sensitivity and specificity are low [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, ruptured cysts may present as the water lily sign, crescent sign, air bubble sign, signet ring sign, or combo's sign [ 6 , 9 , 10 ]. Hepatic cysts should also be investigated by abdominal ultrasound or CT scan because liver involvement typically precedes lung involvement [ 4 ]. In this case, the chest-abdomen-pelvis CT scan showed multiple cysts in the lung, mediastinum, and liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that echinococcosis of the pulmonary artery is mainly derived from hepatic hydatid cysts, and when these rupture in the liver or other organs in the abdomen, they invade the inferior vena cava or the hepatic vein. This enables the cyst contents to enter into the blood circulation and cause a pulmonary embolism after entering into the pulmonary artery and its branches through the right atrium and right ventricle [ 4 6 ]. By the time this situation occurs, the hydatid cyst is not usually seen in the right atrium or right ventricle, and most patients will have a history of hepatic hydatid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid disease or echinococcosis is a near‐cosmopolitan anthropozoonosis 1 . In humans, it is secondary to the development of the larval stage of a tapeworm called Echinococcus granulosus 2,3 .…”
Section: Introductionmentioning
confidence: 99%